(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2022)
Adverse side effects of drug-drug interactions induced by human cytochrome P450 (CYP450)inhibition is an important consideration in drug discovery. Mulberry leaves are of broad popular use for food or remedy purposes, which is believed to contain substances that are beneficial for preventing and alleviating diabetes. However, there is a paucity of information about the effect of mulberry leaves on rat CYP450 enzymes activities and the mRNA expression levels in vivo. The present study aimed to investigate the effect of mulberry leaves on activities of rat CYP450 enzymes (CYP3A4, CYP2C8, CYP2C19, CYP2D6, and CYP1A2) through both probe-drug cocktail approach and real-time polymerase chain reaction (RT-qPCR). The pharmacokinetic results indicated that the aqueous extract of mulberry leaves (AML) exhibited induction effects on CYP3A4 activities, and AML exhibited inhibitory effects on CYP1A2, CYP2D6, and CYP2C8, while no obvious effect was observed on CYP2C19 activity. Additionally, the ethanol extract of mulberry leaves (EML) could induce the activities of CYP3A4. In addition, EML exhibited inhibitory effects on CYP1A2, CYP2D6, and CYP2C19, while no significant change in CYP2C8 activity was observed. Accordingly, the level of mRNA expression of five CYP enzymes were consistent with the result of pharmacokinetic. The results of our study may form a practical strategy for assessing CYP-mediated HDI.